Synthesis, pharmacological and physicochemical profiling of antimalarial and antischistosomal N-aryl 3-trifluoromethyl pyrido [1,2-α] benzimidazoles - Mayoka, Godfrey Wabwile (Department of Chemistry, 2019)
Malaria and schistosomiasis represent the two most prevalent parasitic infections with grievous repercussions on the socio-economic development of affected countries, mainly in sub-Saharan Africa and South-East Asia. Despite their ravaging effects, the treatments of these two diseases have been committed to a limited arsenal of drugs that are threatened by resistance. This scenario, therefore, calls for decisive steps being taken towards the discovery and development of novel drugs with the ability to target multiple parasite stages and be efficacious against resistant parasite strains to achieve effective control and treatment of malaria and schistosomiasis. Originating from a World Health Organisation-Tropical Disease Research initiative, a phenotypic whole cell screening was conducted on a commercial library against Plasmodium falciparum whereupon novel hits exemplified by compound 1, embodying a pyridobenzimidazole (PBI) scaffold, were found to portray in vitro potency against both chloroquine sensitive and resistant parasites. Initial medicinal chemistry iterations generated analogues including 2 from which improved in vitro potency and demonstrable in vivo efficacy in a mouse model were observed. In this thesis, further structural diversity around the PBI motif 3 (Figure 1) was pursued with the aim of generating analogues for structure-activity and structure-property relationship studies. Beyond the asexual blood stage activity, the library of compounds generated was also evaluated for activity against the liver and gametocyte stages of Plasmodium. In exploring the probable mechanism of antimalarial action based on their planar morphology and existence of basic centres, the compounds were evaluated for their capacity to disrupt the heme detoxification process, a recognised druggable target in antimalarial drug discovery. Prioritised compounds, based on in vitro potency, were progressed for in vitro drug metabolism and pharmacokinetics assessment, including metabolic stability and cytotoxicity against Chinese hamster ovarian cell lines. Representative compounds were evaluated for their interaction potential with the human ether-a-go-go-related gene (hERG), a potassium ion channel whose inhibition can cause potentially fatal irregular heartbeats due to perturbed repolarisation of the myocardial action potential. In vivo proof-of-concept efficacy and pharmacokinetics studies were carried out on the most promising leads according to a predetermined screening cascade. Arising from this work, structure-activity relationship (SAR) trends were discernible with electron withdrawing substituents on the aromatic side appendage providing active analogues compared to compounds comprising hydrophilic electron-releasing or donating substituents. Following in vitro microsomal metabolic stability analysis, the series displayed moderate to good metabolic stability with compounds incorporating heteroaromatic side groups showing increased susceptibility to biotransformation usually arising from the aromatic ring. In a P. berghei mouse model at an oral dose of 50mg/kg over four consecutive days, two compounds 1j/GMP-19 and 4i/GMP-75 achieved 98% and 99.9% reduction in parasitaemia and led to mean survival days of 12 and 14, respectively, compared to the untreated infected mice which survived for only 6 days. A drug repositioning approach was pursued, exploiting the cellular and biological similarities in the haemoglobin degradation pathways existent in both Plasmodium parasites and schistosomes. Out of the 57 analogues tested, 12 were found to be potent inhibitors of the adult worms (IC50 ≤ 2 µM), with several compounds also displaying potency against the newly transformed schistosomula. Structural features consistent with good antischistosomal potency, interestingly, overlapped with those present in some compounds that also showed good antiplasmodial activity. Prioritised compounds subjected to in vivo efficacy studies in mice infected with schistosomes identified 1b/GMP-09, 1j/GMP-19 and 4i/GMP-75 with modest antischistosomal activity (55- 70% total worm reduction). Metabolic stability and physicochemical properties correlated with observed in vivo efficacy and solubility- limited absorption was implicated to contribute to low in vivo exposure of the compounds. Further profiling of physicochemical parameters revealed the interdependence of the properties and that crystallinity, as measured by the melting point, influenced compound solubility. In summary, the work pursued in this thesis has unravelled the structural features compatible with potent antimalarial and antischistosomal activities of N-aryl substituted 3- trifluoromethyl PBI derivatives. Additionally, structure-property trends of generated analogues have been delineated. The evolvable nature of the structure-activity and structureproperty relationship trends make these compounds appealing as candidates for further optimisation campaigns to impart improvements in physicochemical properties and drug metabolism and pharmacokinetics attributes without abrogating activity. Moreover, having identified the overlap as well as divergence in chemical spaces relating to antimalarial and antischistosomal potencies of these series inspire further investigations into the mechanisms of observed antiparasitic actions. Finally, that this work has identified targets which are panactive across multiple stages of both Plasmodium and schistosomes, and possessing favourable safety profiles, provide an exciting opportunity for pursuing these analogues as antimalarial and antischistosomal leads with the potential for malaria chemoprevention and transmission blocking.